2011
DOI: 10.1111/j.1365-2214.2011.01333.x
|View full text |Cite
|
Sign up to set email alerts
|

Parental fatigue and parenting practices during early childhood: an Australian community survey

Abstract: Fatigue is common, and results suggest that fatigue contributes to adverse parental practices and experiences. However, possible risk factors for higher fatigue were identified in this study, indicating opportunities for intervention, management and support for parents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
105
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(117 citation statements)
references
References 44 publications
7
105
0
5
Order By: Relevance
“…These results are in accordance with data indicating that symptoms of depression are highly associated with the use of maladaptive cognitive coping, strategies such as rumination [50,51] and self-blame [50]. Furthermore, studies have demonstrated that self-blame is associated with parental perception of less family strength [52] and with increased parental fatigue [53]. A decrease of rumination after Mini-KiSS Online was observed for mothers only, while fathers improved between the post-and follow-up measurements.…”
Section: Discussionsupporting
confidence: 79%
“…These results are in accordance with data indicating that symptoms of depression are highly associated with the use of maladaptive cognitive coping, strategies such as rumination [50,51] and self-blame [50]. Furthermore, studies have demonstrated that self-blame is associated with parental perception of less family strength [52] and with increased parental fatigue [53]. A decrease of rumination after Mini-KiSS Online was observed for mothers only, while fathers improved between the post-and follow-up measurements.…”
Section: Discussionsupporting
confidence: 79%
“…The parents performed considerable demanding care work to help their children get to sleep, while they themselves often experienced reduced or disturbed sleep, leaving them tired and exhausted. This was also highlighted in other studies (Cooklin, Giallo, & Rose, 2012; Giallo, Rose, Cooklin, & McCormack, 2013; Giallo, Rose, & Vittorino, 2011), and is something that can be seen in the context of the experience of fatigue among parents, including after the first few years of a child’s life (Cooklin et al, 2012). It is known that sleep problems in small children can be emotionally difficult for mothers (Hiscock et al, 2008).…”
Section: Discussionsupporting
confidence: 54%
“…To assess parenting self-efficacy, the Parenting Sense of Competence (PSOC) Scale is used [2,21]. PSOC consisted of two subscales, which could be scored either separately or combined for a total score, with higher scores indicating a greater perception of parenting competence.…”
Section: Instrumentmentioning
confidence: 99%
“…More than 85% of women aged 25 to 29 are working women, and 65% of married women have jobs [1]. Although this phenomenon enriches the life of the mothers, it might lead to the mother's lack of time and energy to effectively parenting the child, especially when her child is young [2]. In Macau, about 21% of the workforce is engaged in the tourism and entertainment industry, and 85% of them need to work in shifts [1].…”
Section: Introductionmentioning
confidence: 99%